The Relationship Between Periodontitis Severity and MCP-1, IL-6 Levels in Gingival Crevicular Fluid - misanjas, misanjas; Faisal Ali, Mohammed; Ibrahim Taha, Ghada ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
Periodontitis is an inflammatory disorder that affects the teeth’s supporting structures, leading to attachment loss and bone resorption. Cytokines produced by immune and non-immune cells regulate the immune response, acting as both pro-inflammatory and anti-inflammatory agents. This complex pathogenesis presents a significant public health challenge, emphasizing the need for early and accurate diagnostics. This study aimed to measure volume of gingival crevicular fluid (GCF) using Periotron® and assess potential biomarkers (MCP-1 and IL-6) to predict periodontal disease severity and progression using the Human Enzyme-linked immunosorbent Assay (ELISA). GCF samples were collected from 30 patients with stage 1 periodontitis, 30 patients with stage 3 periodontitis, and 30 healthy subjects. The level of GCF recorded using Periotron® was 0.04 µl for the healthy control group, 0.10 µl for the stage 1 periodontitis group, and 0.70 µl for the stage 3 periodontitis group. MCP-1 and IL-6 levels in the GCF were significantly higher in the stage 3 periodontitis group compared to the stage 1 periodontitis group and healthy subjects.